2016
DOI: 10.1016/j.hrthm.2015.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate and adverse outcomes in patients with atrial fibrillation: A combined AFFIRM and AF-CHF substudy

Abstract: In patients with a history of atrial fibrillation, an elevated baseline heart rate in sinus rhythm is independently associated with mortality. In contrast, the baseline heart rate in atrial fibrillation is not associated with mortality but predicts hospitalizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…A recent Canadian study reported that heart rate in AF was not associated with mortality, although rates > 114 beats per minute predicted hospitalizations. 84 In cases in which digoxin must be used for rate control of AF/AFL, a target resting heart rate < 100 beats per minute is recommended (see Part 3, Recommendation 4 of the Supplementary Material). 85 Practical tip.…”
Section: Digoxin and Mortalitymentioning
confidence: 99%
“…A recent Canadian study reported that heart rate in AF was not associated with mortality, although rates > 114 beats per minute predicted hospitalizations. 84 In cases in which digoxin must be used for rate control of AF/AFL, a target resting heart rate < 100 beats per minute is recommended (see Part 3, Recommendation 4 of the Supplementary Material). 85 Practical tip.…”
Section: Digoxin and Mortalitymentioning
confidence: 99%
“…While echocardiography is indicated for identification of structural heart diseases [38], sub-cohort B will evaluate its further significance for planning AF treatment. Subcohort C will describe the relationships between heart rate during AF and clinical outcomes in elderly NVAF patients, as the association between heart rate and prognosis remains unclear in contrast to the case for sinus rhythm [39]. This issue becomes more important in this specific population because most elderly NVAF patients are under rate-control strategies and at high risk for heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Even so, a post hoc pooled analysis of subjects from the AF-CHF trial and Atrial Fibrillation Follow-up Investigation of Rhythm Management (AFFIRM) study demonstrated an increased association for hospitalizations, but not mortality, for AF subjects with resting heart rate >114 beats/min compared to those 90-114 beats/min. 13 Notably, outcomes were similar between groups with heart rates >114 beats/min and ࣘ76 beats/min for mortality, hospitalizations, and sudden cardiac death. Subjects with tachycardia-induced cardiomyopathy were also likely underrepresented in the Controlled Study of Rate versus Rhythm Control in Patients with Chronic Atrial Fibrillation and Heart Failure (CAFÉ-II) where the resting heart rate at enrollment was 76 ± 14 beats/min.…”
Section: Discussionmentioning
confidence: 86%
“…In fact, these subjects were specifically excluded in the design of the Atrial Fibrillation and Congestive Heart Failure (AF‐CHF) trial . Even so, a post hoc pooled analysis of subjects from the AF‐CHF trial and Atrial Fibrillation Follow‐up Investigation of Rhythm Management (AFFIRM) study demonstrated an increased association for hospitalizations, but not mortality, for AF subjects with resting heart rate >114 beats/min compared to those 90–114 beats/min . Notably, outcomes were similar between groups with heart rates >114 beats/min and ≤76 beats/min for mortality, hospitalizations, and sudden cardiac death.…”
Section: Discussionmentioning
confidence: 99%